Program book : the 2nd annual international conference on Social Sciences and Humanities (AICOSH) 2020 - Program_book_:_the_2nd_annual_international_conference_on_Social_Sciences_and_Humanities_(AICOSH)_20 (Faculty of Social Sciences and Humanities State Islamic University Sunan Kalijaga Yogyakarta, 2020)
st,1/irh,c.1